2000
DOI: 10.1177/030089160008600305
|View full text |Cite
|
Sign up to set email alerts
|

Delay in Diagnosis of High-Grade Osteosarcoma of the Extremities. Has it any Effect on the Stage of Disease?

Abstract: In 965 patients with high-grade osteosarcoma of the extremities, we investigated the correlation between diagnostic delay and the stage of the tumor at presentation. The mean interval between the onset of first symptoms and the final diagnosis was significantly shorter in patients with metastatic disease than in patients with localized disease at the time of the diagnosis. The difference was due to a late presentation of patients with localized disease to the physician and not to delays in performing radiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 8 publications
1
28
1
3
Order By: Relevance
“…Results similar to ours have been reported from the Memorial Sloan-Kettering Cancer Center, where only 11% of 62 patients with clinically detectable metastasis at initial presentation survived, 44 and the Rizzoli Institute, where the chance for 44 patients with primary lung metastases to be alive after 5 years was only 14%. 45 Other than Bacci et al, 46 who recently reported primary spread to be associated with shorter prediagnostic symptom duration and hypothesized about a more aggressive biologic behavior, we found primary metastases to be associated with prolonged symptoms before diagnosis and large size of the primary tumor, which is another indicator of advanced disease. Identical age and sex distributions again argue against basic biologic differences between primary metastatic and seemingly localized osteosarcomas.…”
Section: Bielack Et Alcontrasting
confidence: 61%
“…Results similar to ours have been reported from the Memorial Sloan-Kettering Cancer Center, where only 11% of 62 patients with clinically detectable metastasis at initial presentation survived, 44 and the Rizzoli Institute, where the chance for 44 patients with primary lung metastases to be alive after 5 years was only 14%. 45 Other than Bacci et al, 46 who recently reported primary spread to be associated with shorter prediagnostic symptom duration and hypothesized about a more aggressive biologic behavior, we found primary metastases to be associated with prolonged symptoms before diagnosis and large size of the primary tumor, which is another indicator of advanced disease. Identical age and sex distributions again argue against basic biologic differences between primary metastatic and seemingly localized osteosarcomas.…”
Section: Bielack Et Alcontrasting
confidence: 61%
“…Total pack years has been found to be correlated with a higher risk of developing lung cancer. 31,34 Our patient's 25.5 pack year history placed her at a 3.5 times higher risk of developing lung cancer compared to a non-smoker. 35 Overall, persons who have smoked any amount are at 2.7-8.2 times higher risk of developing lung cancer compared to those who have never smoked.…”
Section: Discussionmentioning
confidence: 82%
“…39 Research has shown that lung cancer risk in former smokers is inversely proportional to number of years since quitting. 31 Despite recommendations from multiple medical providers, our patient never pursued smoking cessation. While several components of this patient's history and physical examination were consistent with a mechanical musculoskeletal dysfunction, the location of the patient's symptoms (upper lumbar spine) was concerning.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations